MODERNIZATION OF THE APPARATUS FOR TESTING CARBON ANODE SAMPLES IN THE ALUMINIUM INDUSTRY - Detiček, Edvard; Kastrevc, Mitja (Journal of Energy Technology, 2024)
The proper quality of carbon anodes is an important factor in the production of aluminium. The deterioration of anode quality disturbs the electrolysis cell conditions and may cause the pot to overheat. The alumina cover has to be reduced in order to lower the bath temperature, which leads to an excessive air burn attack of the anodes and thus to higher carbon consumption, which increases operating costs. Testing of anodes is therefore an important tool to optimize performance and to reduce the costs of aluminium production. This article presents a modernization of the apparatus for testing carbon anode samples with the introduction of dynamic testing.